Preparation And Properties Of Rubber Seed Shell Flour (RSSF)- Filled Polypropylene (PP) Composites - Shafiq, Mohamad Danial (2014)

(untitled)
In this research, rubber seed shell flour (RSSF) was incorporated in polypropylene (PP) to determine the composites with optimum properties. RSSF loadings were varied from 10 php to 40 php to study the effect of adding RSSF on processing, tensile, morphological, flexural, impact, water absorption and thermal properties of PP/RSSF composites. Dalam penyelidikan ini, serbuk kulit biji getah (RSSF) telah ditambahkan dalam polipropilena (PP) untuk menghasilkan komposit dengan ciri-ciri yang optimum. Muatan RSSF diubah dari 10 php hingga 40 php untuk dikaji kesan penambahan RSSF terhadap sifat-sifat pemprosesan, tensil, morfologi, lenturan, hentaman, penyerapan air dan sifat haba bagi komposit.